The Tasawwuf As the Character Education Solution in Indonesia - Baharuddin, Baharuddin; Resky, Muhammad; Soltani, Beya; Ali Madi, Ahmed Abdelraziq (Universitas Darussalam Gontor, 2024)
The research aims to analyse the importance of Sufism values as a solution and improvement of character education in Indonesia. The research method used is a qualitative method with a literature study approach. The data collected in this study were books and journals analysed using the content analysis method. Data analysis was conducted qualitatively through description, reduction, categorisation, and interpretation. This research has shown the importance of Sufism values used in the education and learning system to grow students' moral skills at school. Sufism values are very relevant to the substance of the teachings of the Qur'an and Sunnah to control morals. This research is expected to have implications for systematic efforts in fostering and instilling the character values of piety in students through social behaviour and spiritual attitudes as a provision for life.